Cold shores in warming times - current state and future challenges in High Arctic coastal geomorphological studies - Strzelecki, Mateusz (Quaestiones Geographicae, 2011)
Many of the existing intellectual paradigms regarding the functioning of the polar coastal zone are now out-dated, based on descriptive geomorphology and a limited process-based understanding. Currently, among many components of Arctic landscape adjusting to global warming, the coastal zone is probably the most critical one both in terms of rapidity of environmental change as well as importance for human communities living in circumpolar regions. This issue was often raised during the 4th International Polar Year 2007-2008 and encouraged the scientific community to focus on the state of cold region coasts in more detail. In this paper I summarize the most recent developments in Arctic coastal geomorphology with a particular focus on the Svalbard Archipelago and draw attention to the research challenges awaiting further investigation. This paper highlights the need for a greater understanding of the controls on High Arctic coastal geoecosystems, especially given the potential for accelerated warming and sea-level rise in the coming decades and centuries. Many of presented views benefited from discussions with Professor Andrzej Kostrzewski - to whom this volume is dedicated.